ANALYSIS OF FACTORS INFLUENCING THE CONSUMPTION OF READY-TO-EAT SNACK FOODS IN SOUTH ZONE OF CHENNAI - K. Chitrambigai; G. Sujatha; A. Serma Saravana Pandian; J. Shilpa Shree (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Factors influencing the consumption of ready-to-eat snack foods were analysed through principal component analysis. The data for the study was collected through a well- designed pre-tested interview schedule from 90 respondents in south zone of Chennai. Ten variables were considered as emphasizing factors. The results indicated that the economic factors such as cost saving, quantity and taste are the major influential factors for the consumption of ready-to-eat snack foods in first dimension. In second dimension, habitual factors such as habit, lack of cooking skill and hectic life style are the major influential factors. Convenience factors such as convenience and affordability are the influential factors in third dimension. In fourth dimension, marketing factors such as advertisement and influence of children are the major influential factors among ten variables. The Transparent Market Research (TMR) and the high convenience quotient of ready-to-eat snacks fuels a strong growth for the Ready-to-eat snacks in the market.